Analysis of Modes of Asynchronized Generator in Extra-High Voltage Power Grid - Покровський, Костянтин; Маврін, Ольгерд; Музичак, Андрій; Олійник, Володимир; Pokrovskyi, Kostiantyn; Muzychak, Andriy; Mavrin, Olgerd; Oliinyk, Volodymyr (Lviv Politechnic Publishing House, 2019)
Застосування мереж надвисокої напруги призводить до низки проблем з компенсацією надлишкової реактивної потужності. Варіантом розв’язання таких проблем може бути застосування асинхронізованих генераторів, які мають ряд переваг перед традиційними синхронними генераторами. Ці переваги здебільшого проявляють себе в умовах роботи генератора у мережах із надлишковою реактивною потужністю. Типовим прикладом такої мережі є мережа надвисокої напруги “Острова БуТЕС” та енергомоста “Україна- ЄС”. У роботі наведено результати математичного моделювання режимів мережі “Енергомоста “Україна – ЄС”. Координати режимів визначалися для різних варіантів схеми та режимів роботи генератора. Отримані результати доводять можливість та ефективність пропонованого технічного рішення.

The mathematical model of the air conditioning system has been developed. It is based on the analysis of thermoeconomic energy efficiency indicators and it is solved in a complex way: by defining the optimal parameters taking into account the non-stationary heat of the tides and by determining the optimal device for optimizing the operating modes of the refrigeration system. When designing an air-conditioning system, a thermoeconomic analysis was made for an object being created. An important problem of energy saving was solved during the design with taking into account the changes in electricity tariffs. The thermoeconomic model of the refrigeration unit of the air conditioning system with the definition of exergetic indices and exergic losses has been developed. These indices and losses are components of the thermodynamic efficiency criterion for energy systems that provide a minimum of reduced costs. Analysis of the model allowed obtaining an analytical decision, on the basis of which we can determine the optimal conditions for designing this air conditioning system and its operating modes.
Аналіз режимів асинхронізованого генератора у мережі надвисокої напруги
Keywords: асинхронізований генератор; асинхронізований режим; асинхронний режим; надвисоковольтна мережа; енергоміст “Україна–ЄС”; exergy; analysis; thermoeconomic optimization; air conditioning; refrigeration units; electricity tariffs; heat exchange